\(\dfrac{y+5}{3}\)= \(\dfrac{56}{21}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\dfrac{-3}{5}+\dfrac{28}{5}.\left(\dfrac{43}{56}+\dfrac{5}{24}-\dfrac{21}{63}\right)\)
= \(\dfrac{-3}{5}+\dfrac{28}{5}.\dfrac{9}{14}\)
= \(\dfrac{-3}{5}+\dfrac{28.9}{5.14}\)
= \(\dfrac{-3}{5}+\dfrac{18}{5}\)
= \(\dfrac{\left(-3\right)+18}{5}\)
= \(\dfrac{15}{5}=3\)
![](https://rs.olm.vn/images/avt/0.png?1311)
cho mình nghi lại nha mn \(\dfrac{-3}{5}+\dfrac{28}{5}\cdot\left(\dfrac{43}{56}+\dfrac{5}{24}-\dfrac{21}{63}\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\dfrac{1}{3}+\dfrac{1}{7}+\dfrac{1}{5}+\dfrac{32}{40}+\dfrac{48}{56}+\dfrac{14}{21}\\ =\dfrac{1}{3}+\dfrac{1}{7}+\dfrac{1}{5}+\dfrac{4}{5}+\dfrac{6}{7}+\dfrac{2}{3}\\ =\left(\dfrac{1}{3}+\dfrac{2}{3}\right)+\left(\dfrac{1}{7}+\dfrac{6}{7}\right)+\left(\dfrac{1}{5}+\dfrac{4}{5}\right)\\ =1+1+1=3\)
Lời giải:
$\frac{1}{3}+\frac{1}{7}+\frac{1}{5}+\frac{32}{40}+\frac{48}{56}+\frac{14}{21}$
$=\frac{1}{3}+\frac{1}{7}+\frac{1}{5}+\frac{4}{5}+\frac{6}{7}+\frac{2}{3}$
$=(\frac{1}{3}+\frac{2}{3})+(\frac{1}{7}+\frac{6}{7})+(\frac{1}{5}+\frac{4}{5})$
$=\frac{3}{3}+\frac{7}{7}+\frac{5}{5}=1+1+1=3$
![](https://rs.olm.vn/images/avt/0.png?1311)
a: 3/8=36/96
5/12=40/96
b: -2/9=-24/108
-5/12=-45/108
c: -3/16=-63/336
-5/24=-70/336
-21/56=-126/336
![](https://rs.olm.vn/images/avt/0.png?1311)
a) Ta có: \(\dfrac{5}{8}+\dfrac{3}{17}+\dfrac{4}{18}+\dfrac{20}{-17}+\dfrac{-2}{9}+\dfrac{21}{56}\)
\(=\left(\dfrac{3}{17}-\dfrac{20}{17}\right)+\left(\dfrac{2}{9}-\dfrac{2}{9}\right)+\left(\dfrac{5}{8}+\dfrac{3}{8}\right)\)
\(=-1+1=0\)
b) Ta có: \(\left(\dfrac{9}{16}+\dfrac{8}{-27}\right)+\left(1+\dfrac{7}{16}+\dfrac{-19}{27}\right)\)
\(=\left(\dfrac{9}{16}+\dfrac{7}{16}\right)+\left(\dfrac{-8}{27}-\dfrac{19}{27}\right)+1\)
=1-1+1=1
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{-3}{5}+\frac{28}{5}.(\frac{43}{56}+\frac{5}{24}-\frac{21}{63})\)
=\(\frac{-3}{5}+\frac{28}{5}.(\frac{43}{56}+\frac{5}{24}-\frac{1}{3})\)
=\(\frac{-3}{5}+\frac{28}{5}.(\frac{129+35-56}{168})\)
=\(\frac{-3}{5}+\frac{28}{5}.\frac{9}{14}\)
=\(\frac{-3}{5}+\frac{28.9}{5.14}\)
=\(\frac{-3}{5}+\frac{2.9}{5.1}\)
=\(\frac{-3}{5}+\frac{18}{5}\)
=3
![](https://rs.olm.vn/images/avt/0.png?1311)
Bài 1:
$(y+\frac{1}{3})+(y+\frac{1}{9})+(y+\frac{1}{27})+(y+\frac{1}{81})=\frac{56}{81}$
$(y+y+y+y)+(\frac{1}{3}+\frac{1}{9}+\frac{1}{27}+\frac{1}{81})=\frac{56}{81}$
$4\times y+\frac{40}{81}=\frac{56}{81}$
$4\times y=\frac{56}{81}-\frac{40}{81}=\frac{16}{81}$
$y=\frac{16}{81}:4=\frac{4}{81}$
Bài 2:
$18: \frac{x\times 0,4+0,32}{x}+5=14$
$18: \frac{x\times 0,4+0,32}{x}=14-5=9$
$\frac{x\times 0,4+0,32}{x}=18:9=2$
$x\times 0,4+0,32=2\times x$
$2\times x-x\times 0,4=0,32$
$x\times (2-0,4)=0,32$
$x\times 1,6=0,32$
$x=0,32:1,6=0,2$
\(\dfrac{y+5}{3}=\dfrac{8}{3}\)
y + 5 = 8
y = 3